Pin on flat wear volume prediction of UHMWPE against cp Ti for orthopedic applications - Handoko, Handoko; Suyitno, Suyitno; Rini, Dharmastiti; Rahadyan, Magetsari (2018)
Tribological assessment of orthopedic biomaterials requires a lot of testing time. Researchers must test the biomaterials in millions of cycles at low frequency (1 Hz) to mimic the in vivo conditions. It is a problem because product designs and developments could not wait longer for wear data to predict the lifetime of their products. The problem can be solved with the use of computation techniques to model the wear phenomena and provide predicted data. The aim of this research is to predict the wear volume of the commonly used ultra high molecular weight polyethylene (UHMWPE) sliding against commercially pure titanium (cp Ti) in the unidirectional pin on flat tests. The 9 mm diameter UHMWPE pin and cp Ti plate contact mechanics were modeled using Abaqus. Contact pressure was set at 3 MPa. Outputs of the computations (contact pressure and contact area) were used to calculate the wear volume with Archard law. A custom Python script was made to automate the process. The results were then compared with experimental data for validations. The predicted data were in a good trend with numerical errors from 0.3% up to 26%.